Hope and death obsession after the Maras earthquake: Psychological inflexibility and psychache as serial mediators - Aktepe, Zahide Gul; Deniz, M. Engin; Eris, Yavuz; Birni, Gaye; Satici, Begum; Kaya, Yagmur (ELSEVIER, 2025)
The earthquake is not only a destruction of buildings, but also a shattering of people's mental states. How survivors regulate dysfunctional feelings and thoughts toward death in the aftermath of an earthquake is a matter of curiosity. Therefore, this study examined the role of hope, psychological inflexibility, and psychache, which will provide a better understanding of people's obsession with death after the earthquake in Turkey. Participants were 419 Turkish individuals aged 18-59 years from 61 cities in Turkey. Structural equation modeling was performed. The findings showed the full mediation model that psychological inflexibility and psychache had significant mediating roles in the relationship between hope and death obsession, respectively. Whether directly or indirectly, increased hope is associated with less psychological inflexibility and less psychache among earthquake survivors. Positive and healing potentials of hope and psychological flexibility in reducing obsession with death in individuals with earthquakes or other traumatic experiences have been revealed.
Keywords: Psychological inflexibility; Psychache; Hope; Death of obsession; Earthquake survivors; POSTTRAUMATIC-STRESS-DISORDER; QUALITY-OF-LIFE; MENTAL-HEALTH; DEPRESSION; DISTRESS; SUICIDE; PREVALENCE; RESILIENCE; VALIDATION; EXPOSURE; Geology; Meteorology & Atmospheric Sciences; Water Resources